Avaliação de sistemas agroflorestais utilizando indicadores agroecológicos de sustentabilidade - Trindade, Maeli Oliveira (2022)
Agroforestry Systems (SAFs) are recommended because they contribute to an area returning to its initial landscape, given that they contribute to the conservation of biodiversity and restore the provision of ecosystem services. The objective of this study was to evaluate, through the application of a set of ecological indicators of sustainability, if the agroforestry systems implemented for restoration and agroecological production in the areas of Sitio São João, promoted the return of the ecological functions of the local ecosystem. For this, a protocol with ecological indicators was adapted and applied in two Agroforestry Systems and an adjacent riparian forest, in order to relate to their ecological functionality, which in turn is associated with the return and maintenance of ecological processes provided by: species diversity, functional diversity, development of individuals, system control and management and soil protection and nutrient cycling, agrobiodiversity, socioeconomic aspects and satisfaction. The two SAFs stood out positively in at least one ecological functionality descriptor. The SAFs added an average of 37 points, that is, they recovered on average the corresponding to 64.95% of the ecological functionality in relation to the positive and referential scenarios, ranging between 66.7% and 63.2%, for the SAFs 1 and 2. SAF1 showed better functioning and one of the explanations is the characterization of each area, where SAF1 was more biodiverse compared to SAF2. This can be explained by the type of management I carry out in each area, as well as the choice of species and the functions generated by them.